Fiducia e argomentazione. Una prospettiva aristotelica - Di Piazza, Salvatore (Rivista Italiana di Filosofia del Linguaggio, 2012)
Trust and argumentation. An Aristotelian perspective. Through a re-reading of some Aristotelian works we propose to investigate the relationship between trust, argumentation and persuasion. In particular, we will analyze the Greek notion of pistis, that can also be translated as “trust”. The underlying idea is that speakers persuade audiences not always through the substance of their arguments but rather through their perceived trustworthiness, sometimes regardless of how “rational” the arguments actually are.